2014
DOI: 10.1016/j.amjmed.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IT-enabled Intervention on MRI Use for Back Pain

Abstract: Background Examine the impact of a multi-faceted, clinical decision support (CDS)-enabled intervention on magnetic resonance imaging (MRI) use in adult primary care patients with low back pain. Methods After a baseline observation period, we implemented a CDS targeting lumbar-spine MRI use in primary care patients with low back pain through our computerized physician order entry (CPOE) as well as two accountability tools: 1) mandatory peer-to-peer consultation when test utility was uncertain and 2) quarterly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…Our findings are consistent with those of earlier studies that reported that CDS interventions that allow simple override are unlikely to optimize provider behavior during the imaging ordering process (33). Stronger interventions, such as requiring clinical justification for overriding CDS alerts (34), implementing physician performance feedback reports (35), or requiring real-time peer-to-peer consultation for providers who ignore evidence presented in CDS alerts (36), have increased adherence to evidence presented in CDS. Mandating d-dimer testing before CT pulmonary angiography for patients unlikely to have PE may be another potential strategy to further reduce the unnecessary use of CT pulmonary angiography.…”
Section: Yield Of Pe In Patients Unlikely To Have Pesupporting
confidence: 82%
“…Our findings are consistent with those of earlier studies that reported that CDS interventions that allow simple override are unlikely to optimize provider behavior during the imaging ordering process (33). Stronger interventions, such as requiring clinical justification for overriding CDS alerts (34), implementing physician performance feedback reports (35), or requiring real-time peer-to-peer consultation for providers who ignore evidence presented in CDS alerts (36), have increased adherence to evidence presented in CDS. Mandating d-dimer testing before CT pulmonary angiography for patients unlikely to have PE may be another potential strategy to further reduce the unnecessary use of CT pulmonary angiography.…”
Section: Yield Of Pe In Patients Unlikely To Have Pesupporting
confidence: 82%
“…Our findings support the notion that these information-only CDS interventions are unlikely to optimize provider test-ordering practices [20, 21]. A few interventions use a “hard stop,” preventing users from placing orders that conflict with evidence presented in the CDS until completion of additional, more intrusive software-enabled workflows, such as requiring responsible clinicians to personally log in and order examinations rather than relying on proxy ordering by nonclinician support staff [5] or mandating peer-to-peer consultation to override alerts [6]. However, those who implement CDS are cautioned to avoid hard stop interventions in all but the most dire circumstances [22] because physicians strongly resist such interventions [23] and are more likely to ignore serious, life-threatening alerts when alert presentation does not differ by potential clinical impact [24].…”
Section: Discussionmentioning
confidence: 99%
“…In medical imaging, CDS tools are typically triggered at the time of order entry to guide ordering providers in selecting the optimal imaging strategy (or no imaging at all) [1]. Although best practices for effective imaging CDS may be debated, the successful implementation and early impact of CDS, including systems guiding imaging orders [26], has led to the incorporation of CDS provisions into two sets of federal regulations. The first provides modest financial incentives for adoption of CDS as a major focus of meaningful-use stage II regulation for health care information technology [7], and the second mandates the use of imaging CDS for targeted ambulatory procedures beginning January 1, 2017, as part of the Protecting Access to Medicare Act of 2014 [8].…”
mentioning
confidence: 99%
“…One study assessed clinical decision support in a hospital outpatient clinic and found a statistically significant decrease in imaging in the intervention group. 33 The other assessed guideline distribution with audit and feedback and found no statistically significant results. 15 These results are consistent with those found in our review.…”
Section: Limitationsmentioning
confidence: 99%
“…The authors found a statistically significant decrease in referrals for imaging of the spine (risk ratio 0.7, 95% CI 0.5 to 0.95); however, they did not account for clustering in the initial analysis, which decreased the validity of the result. We excluded 2 controlled before-after studies 33,15 because of study design. One study assessed clinical decision support in a hospital outpatient clinic and found a statistically significant decrease in imaging in the intervention group.…”
Section: Limitationsmentioning
confidence: 99%